A Dioxane Template for Highly Selective Epoxy Alcohol Cyclizations. Issue 30 (17th June 2013) - Mousseau, James J.; Morten, Christopher J.; Jamison, Timothy F.
Abstract Ladder polyether natural products are a class of natural products denoted by their high functional‐group density and large number of well‐defined stereocenters. They comprise the toxic component of harmful algal blooms (HABs), having significant negative economic and environmental ramifications. However, their mode of action, namely blocking various cellular ion channels, also denotes their promise as potential anticancer agents. Understanding their potential mode of biosynthesis will not only help with developing ways to limit the damage of HABs, but would also facilitate the synthesis of a range of analogs with interesting biological activity. 1, 3‐Dioxan‐5‐ol substrates display remarkable 'enhanced template effects' in water‐promoted epoxide cyclization processes en route to the synthesis of these ladder polyether natural products. In many cases, they provide near complete endo‐to‐exo selectivity in the cyclization of epoxy alcohols, thereby strongly favoring the formation of tetrahydropyran (THP) over tetrahydrofuran (THF) rings. The effects of various Brønsted and Lewis acidic and basic conditions are explored to demonstrate the superior selectivity of the template over the previously reported THP‐based epoxy alcohols. In addition, the consideration of other synthetic routes are also considered with the goal of gaining rapid access to a plethora of potential starting materials applicable towards the synthesis of ladder polyethers. Finally, cascade sequences with polyepoxides are investigated, further demonstrating the versatility of this new reaction template.